Synergistic Anti-Tumor Effect of Combining Selective CDK7 and BRD4 Inhibition in Neuroblastoma - Gao, Yang; Volegova, Marina; Nasholm, Nicole; Das, Sanjukta; Kwiatkowski, Nicholas; Abraham, Brian J.; Zhang, Tinghu; Gray, Nathanael S.; Gustafson, Clay; Krajewska, Malgorzata; George, Rani E. (Frontiers in Oncology, 2022)
Purpose: Cyclin-dependent kinases (CDKs) that have critical roles in RNA polymerase II (Pol II)-mediated gene transcription are emerging as therapeutic targets in cancer. We have previously shown that THZ1, a covalent inhibitor of CDKs7/12/13, leads to cytotoxicity in MYCN-amplified neuroblastoma through the downregulation of super-enhancer-associated transcriptional upregulation. We sought to dissect the mechanisms of cytotoxicity in NB cells and to identify additional targets that could be inhibited together with CDK7 in combination therapy. Experimental Design: We used YKL-5-124, a novel covalent CDK7 inhibitor with greater selectivity compared to THZ1, to determine the effect of CDK7 inhibition in neuroblastoma cells. Results: CDK7 inhibition with YKL-5-124 did not lead to significant cell death, but resulted in aberrant cell cycle progression. Unlike THZ1, YKL-5-124 had minimal effects on Pol II C-terminal domain phosphorylation, but significantly inhibited that of CDK1 and CDK2 cell cycle kinases. Combining YKL-5-124 with the BRD4 inhibitor JQ1 resulted in synergistic cytotoxicity. A distinct gene expression signature associated with resistance to BRD4 inhibition was suppressed with the combination. The synergy between YKL-5-124 and JQ1 translated into significant tumor regression in cell line and patient-derived xenograft mouse models of neuroblastoma. Conclusions: The combination of CDK7 and BRD4 inhibition provides a therapeutic option for neuroblastoma and suggests that the addition of YKL-5-124 could improve the therapeutic efficacy of JQ1 and delay resistance to BRD4 inhibition.